The lesser gods of the Sahara : social change and contested terrain amongst the Tuareg of Algeria - Keenan, Jeremy, 1945- (Frank Cass, 2004)
The eight essays that comprise this collection cover various aspects of social change and contested terrain amongst the Tuareg people Algeria.
Keywords: Tuaregs -- History.; Tuaregs -- Ethnic identity.; Tuaregs -- Social life and customs.; Social change -- Algeria.; Cultural property -- Protection -- Algeria.; Algeria -- Colonization.; Algeria -- Race relations.; Algeria -- Politics and government.; Touaregs -- Histoire.; Touaregs -- Identité ethnique.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Colonization; Cultural property -- Protection; Politics and government; Race relations; Social change; Tuaregs; Tuaregs -- Ethnic identity; Tuaregs -- Social life and customs; Algeria; Electronic books.; History